Strategies to address stigma and discrimination of people with HIV/AIDS through community system strengthening - Akbar, M Agung (Science Center Group, 2024)
The COVID-19 pandemic has diverted attention from the HIV/AIDS epidemic, despite the ongoing need for substantial attention. In Indonesia, HIV/AIDS cases continue to fluctuate, with a significant cumulative number, highlighting the importance of community involvement in prevention and treatment efforts. The main barrier to addressing HIV/AIDS is the stigma and discrimination faced by People Living with HIV/AIDS (PLWHA), which hinders their access to healthcare services and social support. This article examines the approach of Community System Strengthening as a strategy to reduce stigma and discrimination against PLWHA. Through education, community involvement, and continuous counseling, it is hoped that society can become more supportive and reduce the social stigma PLWHA face. This study also provides community-based intervention guidelines as a solution to enhance the health and well-being of PLWHA in Indonesia.